Respuesta :
solve for x:-
f(x) = 4x + 8
4x = f(x) - 8
x = (f(x) - 8)/4
f-1(x) = (x - 8)/4 <------- the inverse
f(x) = 4x + 8
4x = f(x) - 8
x = (f(x) - 8)/4
f-1(x) = (x - 8)/4 <------- the inverse
An inverse function simply produces points (y,x) for each point (x,y) of the parent function. So to find an inverse function you must solve for the independent variable and then simply sway the variable labels...
y=4x+8 so we want to solve for x, subtract 8 from both sides
y-8=4x, divide both sides by 4
(y-8)/4=x, now simply swap variable labels...
y=(x-8)/4
f^-1(x)=(x-8)/4
y=4x+8 so we want to solve for x, subtract 8 from both sides
y-8=4x, divide both sides by 4
(y-8)/4=x, now simply swap variable labels...
y=(x-8)/4
f^-1(x)=(x-8)/4